Project papers on marketing: Cool-Aire Philippines, Inc. case management control: Philippine Machinery Corporation case investment management: Island Machinery Company, Inc. case - Santiago, Angel M., Jr. (Animo Repository, 1974)
On January 18, 1973, Fuji WInd, CPI's strongest competitor in package air-conditioning (PAC), reportedly sold to the commercial segment of the market some 2,000 units of the 3-TR model in 1972, easily accounting for about half the total market for PAC systems. Contrary to this report, Mr. Ben Romero, CPI's sales manager for PAC systems, estimated the 1972 total sales of the 3-TR model at a maximum of only 1,000 units. Nevertheless, considering that two years before, sales of this size unit was practically nil, there was a strong reason for CPI to be alarmed, especially since they sold only 30 units of the 3-TR model in 1972.In 1972, CPI had a 17 percent (2,200 TR) share of the total PAC market, second only to Fuji Wind's 50 percent (6,500 TR). While CPI's provincial sales was only 7 percent of its total. Fuji Wind sold 2,500 TR (or 38 percent of its total) in the provinces through its nationwide network of dealers that also carried its complete line of appliances. Through this dealership network, Fuji Wind was able to funnel into its clientele, almost all switchers to PAC, from the users of room or window-type air conditioners (mostly from the commercial segment). CPI on the other hand, was a natural catcher of switchers to PAC, from the users of type air conditioning systems, owing to the image and good it has created in this (industrial) segment of the market. Without much regard for the development efforts of Fuji Wind in creating the demand for the 3-TR, Mr. Romero reacted by formulating a plan designed to capture a substantial portion of this demand, mainly by commissioning dealers and engineering firms to sell and install CPI's 3-TR unit. Despite a lower-than-standard profit margin in their present 3-TR model, Mr. Romero wanted to market it anyway because of the incremental profit it was expected to contribute. Furthermore, in the race for the biggest share of the PAC market, Mr. Romero felt that the 3-TR can be instrumental in giving CPI back the lead position. On the other hand, Mr. Jaime Alberto,